1972
DOI: 10.1002/bjs.1800590302
|View full text |Cite
|
Sign up to set email alerts
|

The battered buttock syndrome-fat fractures a report on a group of traumatic lipomata

Abstract: A group of 12 women with traumatic fat swellings around the buttock region is presented.2. The structure of the subcutaneous tissue and the mechanism in formation of the lipomata are described.3. Treatment of the essentially cosmetic deformity is discussed and excision of the lipomatous mass is advised when symptoms indicate this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 0 publications
1
46
0
Order By: Relevance
“…Deep-seated lipomas should always be taken into consideration when dealing with soft tissue masses. The mechanism for intermuscular lipomas remains unclear, and trauma was reported as a related factor (4,19,20). It was suggested that after a blunt trauma, rupture of the fibrous septa, which prevent the migration of fat, accompanied by tears of the anchorage between the skin and the deep fascia likely resulted in the proliferation of adipose tissue (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep-seated lipomas should always be taken into consideration when dealing with soft tissue masses. The mechanism for intermuscular lipomas remains unclear, and trauma was reported as a related factor (4,19,20). It was suggested that after a blunt trauma, rupture of the fibrous septa, which prevent the migration of fat, accompanied by tears of the anchorage between the skin and the deep fascia likely resulted in the proliferation of adipose tissue (20).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for intermuscular lipomas remains unclear, and trauma was reported as a related factor (4,19,20). It was suggested that after a blunt trauma, rupture of the fibrous septa, which prevent the migration of fat, accompanied by tears of the anchorage between the skin and the deep fascia likely resulted in the proliferation of adipose tissue (20). However, in the present patient, the tumor was believed to have already existed prior to the accident and became evident after being extruded from the surrounding tissues by the trauma, given the limited time period between the trauma and mass formation (20 days).…”
Section: Discussionmentioning
confidence: 99%
“…The initial report as to the possible role of trauma in the development of lipomas dates back to 1932 when Adair et al described two patients with lipomas secondary to trauma (13). This case debates Meggitt and Wilson's hypothesis which suggests that when excessive force is applied locally to adipose tissue, it may cause fat compartments to fracture, shearing of the anchoring between the skin and the deep fascia (14). This leads to pouting of adipose tissue, resulting in PTL after the bruising and haematoma settle down.…”
Section: Discussionmentioning
confidence: 75%
“…Blunt trauma is one of the possible reasons. Rupture of the fibrous tissue after blunt trauma may result in proliferation of the adipose tissue (10). In some cases lipomas are also associated with several syndromes such as Gardner's syndrome, Madelung's disease, and Dercum's disease (1,8).…”
Section: Introductionmentioning
confidence: 99%